(untitled) (Balneo and PRM Research Journal, 2024)
The purchase of a tourist package for a certain tourist destination has become extremely easy and transparent through the diversity and continuously upgraded online booking platforms, inline with sustainable management. Their content provides useful data for tourists and tourism managers but also for researchers or policy makers. Therefore, the study explores data from two global platforms (Booking and TripAdvisor) and a national one (Turistinfo) by analyzing sentiments and emotions in order to identify multidimensional tourists’ satisfaction between 2018 and 2020 for the hotel industry in Northern Oltenia, Romania. For this purpose 10,945 online reviews for 248 accommodation units in the studied area were collected and processed in Statistical Package for the Social Sciences (SPSS 17.0) and Geographical Information System (GIS). The key findings indicate that most travelers are satisfied with tourist destinations, sustained by the dominance of positive emotions (82%) associated with a high rating score (8.9). The higher satisfaction is linked to the quality of five and four stars acommodation units, but also to intimacy of small families business, the spatial framing in the landscape, the friendship the hosts, while the repulsive aspects draw attention to some problems of the state of the indoor or outdoor environment and the price-quality ratio. This study proves the efficiency of looking into electronic word-of-mouth as a source to evaluate tourist satisfaction for stakeholders in tourism to gain faster sustainable options for their accommodation services.